Measuring sustainable indigenous tourism indicators: a case of Mah Meri ethnic group in Carey Island, Malaysia - Kunasekaran, Puvaneswaran; Gill, Sarjit S.; Ramachandran, Sridar; Shuib, Ahmad; Baum, Tom; Mohammad Afandi, Syamsul Herman (MDPI, 2017)
Sustainable tourism emphasises responsible utilisation of economic, socio-cultural and environmental resources for tourism development. Extant literature in sustainable tourism leans towards subjective and qualitative description in explaining the dynamic nature of the trans-disciplinary indicators of sustainability. However, few mechanisms have been proposed or developed to quantify the indicators measuring sustainable tourism in an indigenous ethnic context. The current study measures 61 sustainable indigenous tourism indicators of the Mah Meri ethnic group that comprise three constructs, namely, community resources, community development and sustainable tourism. Simple random sampling was employed for data elicitation and a weighted average score using R software as the basis of analysis was used to produce a sustainable indigenous tourism barometer (SITB). The study identifies 11 sustainability dimensions from the initial three main constructs that are treated as the relationship aspects in this study. Based on the Sustainable Indigenous Tourism Barometer (SITB), community participation, empowerment, economic and socio-cultural sustainability are found to be the main influencing dimensions of sustainability of the Mah Meri ethnic group. However, natural resources, financial resources and environmental sustainability indicated weaker relationships in explaining sustainability of the Mah Meri ethnic group. Based on the SITB, the results demonstrate that the Mah Meri ethnic group are a “potential sustainable” tourism stakeholder.